Assessment of Herpes Simplex Virus Type 1 and 2 by IHC in Association with CD14 Antigen in Placental Tissues from Women with Miscarriage - A. Hamid, Zainab; J. Ali, Solaf; Hattem Hussain, Ali (Kurdistan Journal of Applied Research, 2018)
Among many viral causes of miscarriage, maternal infections caused by herpes simplex virus type -1 (HSV-1) and Herpes simplex virus type-2 (HSV-2) infections are important causes. CD14 was implicated in immune mechanisms, and might be involved in pregnancy loss. The aim of this study was to detect the possible occurrence of two HSV-1 and HSV-2 infections as well as the immunological factor cd14 in placental tissues from patients with spontaneous abortion using immunohistochemistry techniques. Immunohistochemistry technique assay was used to detect placental infection with HSV-1& HSV-2 as well as CD14 in 40 women with spontaneous miscarriage and in 40 healthy deliveries in Baghdad/Iraq. The IHC- expressions of HSV-1, HSV-2, and CD14 proteins were detected in 4(10%), 15(37.5%), 15(37.5%) in placental tissues from miscarriage women, respectively. The association between CD14 with HSV-1 and HSV-2 among the placental tissues from miscarriage patients was constituting (5%), (20%) with HSV-1 & HSV-2, respectively. The considerable proportion of HSV-1, HSV-2, and infections found in the placental tissues from miscarriage women could drag the attention of obstetricians to implicate these viruses as possible targets in the etiology of spontaneous abortion case and there is possible association of CD14 with HSV-1 and HSV-2 in women with abortion.